Serum Wisteria floribunda agglutinin-positive Mac-2 binding protein in non-alcoholic fatty liver disease - Lai, L.L.; Chan, W.K.; Sthaneshwar, P.; Mustapha, N.R.N.; Goh, K.L.; Mahadeva, S. (Public Library of Science, 2017)
Wisteria floribunda agglutinin-positive Mac-2 binding protein (WFA+-M2BP) has been suggested to be useful for the assessment of disease severity in non-alcoholic fatty liver disease (NAFLD). Consecutive adult NAFLD patients who had a liver biopsy were included. Serum WFA+-M2BP level was measured using a lectin-antibody sandwich immunoassay using a chemiluminescence enzyme immunoassay machine (HISCL-5000, Sysmex, Kobe, Japan). The measured levels were indexed using the following equation: Cut-off index (COI) = ([WFA+-M2BP]sample-[WFA+-M2BP]NC) / ([WFA+-M2BP]PC-[WFA+-M2BP]NC), where PC = positive control and NC = negative control. Histopathological examination of liver biopsy specimen was reported according to Non-Alcoholic Steatohepatitis (NASH) Clinical Research Network Scoring System. Data for 220 cases were analyzed. The AUROC of the COI for the diagnosis of NASH was 0.65. The AUROC of the COI for the diagnosis of steatosis grade ≥2 and 3 was 0.64 and 0.53, respectively. The AUROC of the COI for the diagnosis of lobular inflammation grade ≥1, ≥2 and 3 was 0.57, 0.68 and 0.59, respectively. The AUROC of the COI for the diagnosis of hepatocyte ballooning grade ≥1 and 2 was 0.64 and 0.65, respectively. The AUROC of the COI for the diagnosis of fibrosis stage ≥1, ≥2, ≥3 and 4 was 0.61, 0.71, 0.74 and 0.84, respectively. Out of the 220 cases, 152 cases were the same 76 patients who had a repeat liver biopsy after 48 weeks of intervention. The AUROC of the change in the COI to detect improvement in steatosis, lobular inflammation, hepatocyte ballooning and fibrosis was 0.57, 0.54, 0.59 and 0.52, respectively. In conclusion, serum WFA+-M2BP was most useful for the diagnosis of significant fibrosis, advanced fibrosis and cirrhosis in NAFLD patients. However, it was less useful for differentiating NASH from non-NASH, and for diagnosis and follow-up of the individual histopathological components of NASH.